Post-citizenship, the New Left and the democratic commons - Stevenson, Nick (Taylor & Francis, 2015)
This article investigates the possibilities for the emergence of more participatory forms of citizenship in the context of austerity Europe. Especially significant in this regard is the history of the post-war New Left who were critical of both social democracy and authoritarian Marxism. In this context I reconsider the radical ‘humanistic’ writing of E.P. Thompson and Raymond Williams. Not only does their work offer a critical understanding of the commons, but equally connects to the revival of humanism evident within the alter globalisation movement. Further I look at the development of different ideas for a revived Left including nostalgia for the social democratic period and the idea of cosmopolitanism. While all of this work has something to offer I seek to argue that it fails to adequately address the need to develop more ecologically sensitive and more participatory forms of citizenship. In the final section, I outline the importance of the struggle for a more democratic and autonomous society and the increasing importance of issues related to traditions of self-management and the idea of the commoner. The idea of the commoner could yet become one of the major ideological struggles of the twenty-first century, but this will depend upon its ability to excite the imaginations of Europe's increasingly frustrated citizens in the age of neoliberalism.